Manufacturing a Plotter Printer with Computer Numerical Control Based Pen Ink Using CoreXY Mechanisms - Veshea Falerie Goszal; Hilal Hudan Nuha; Maman Abdurohman (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
In the process of printing images, a high-quality plotter printer is required to obtain better printed images. This causes the costs incurred to purchase a plotter printer become even higher along with the quality of the printout. In addition, the use of original plotter printer ink is significantly more expensive than that of the non-original ink. Therefore, this paper proposes a pen based computer plotter printer design using the CoreXY framework. This framework is based on a 2D in-axis motion control technique using a single continuous belt for both axes. To evaluate the performance of the proposed design, the level precision for vector and raster modes are measured using the Mean Absolute Percentage (MAPE). Based on the results of precision measurements, it was found that the printer prototype designed to produce high-precision images with affordable pen ink costs and can process digital instructions from a computer using Computer Numerical Control (CNC).